2014
DOI: 10.1016/j.cub.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Potential Disruption of Pollination in a Sexually Deceptive Orchid by Climatic Change

Abstract: Warmer springs advance many phenological events, including flowering time in plants and the flight time of insects. Pollination by insects, an ecosystem service of immense economic and conservation importance, depends on synchrony between insect activity and flowering time. If plants and their pollinators show different phenological responses to climate warming, pollination could fail. Information about the effects of warming on specific plant-insect mutualisms is difficult to obtain from complex pollination n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 26 publications
4
97
1
2
Order By: Relevance
“…Pollination from both honey bees and native bees is critical for tree fruit and berry crops grown in the Pacific Northwest (Sagili and Caron 2016;Rucker et al 2012). Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Pollination from both honey bees and native bees is critical for tree fruit and berry crops grown in the Pacific Northwest (Sagili and Caron 2016;Rucker et al 2012). Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Leakage is likely when ecosystem discordance arises from lags in activation of microbial community members responsible for sequential steps in a biogeochemical cycle. This is analogous to the uncoupling that occurs when climate warming causes early flowering that is out of sync with insect hatching, leading to pollination failures42. Such phenomena are little known in microbial ecosystems, but could give rise to large fluxes of climate-relevant intermediate compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling effort for specimens is largely unknown. Thus, they represent an imperfect historical record, which researchers have nonetheless been able to successfully use, often combined with creative approaches (e.g., Bartomeus et al, 2013; Robbirt et al, 2014; Matthews and Mazer, 2015). …”
Section: Discussionmentioning
confidence: 99%